Evaluation of Demographic Characteristics and Biochemical Parameters with Echovirus Infection in Children at Thi-Qar Province/Iraq - Al Mousawi, Dalal K.; Hamad, Bushra J. (University of Thi-Qar Journal of Science, 2022)
The current study was conducted in Thi-Qar province, with One hundred blood specimens were collected from patients in Mohammed Al-Mousawi Hospital for Children (ages between 2 days - 3 years, males and females), at the period between November 2021 to February 2022.This study aimed to revealed the relationship between different characteristics (sex, age and clinical symptoms) with viral infections , and diagnosis by WBC COUNT, platelet and C-reactive protein for each patients. Based on the results recorded among 100 children have different disease, but only, 9% of patients were infected with the Echovirus, and 91% were negative for viral infection, the results also noted a significant difference in viral prevalence in children at p. value < 0.05. Results also noted a non-significant difference according to children’ gender at p. value < 0.05. Most children infected with Echovirus was in 6-8 and 8-10 month 25%, while the age groups (3day-< 2 month), (2 - < 4 month), (12 - < 14 month), and (14 - < 16 month), were non-infected with Echovirus. The results also noted a significant difference according to age groups at p. value < 0.05. The results of present study showed that CRP and WBC count were increase, while the platelet count was low or normal in children